Analysis of Work Posture and Work-Related Musculoskeletal Disorders with ROSA Method at Batam Environmental Service - Arinda Soraya Putri; Dwinda Amalia (Universitas Muhammadiyah Sidoarjo, 2021)
Nowadays, computer is widely used in the work field. It is because computers can increase work efficiency and effectiveness. Dinas Lingkungan Hidup (DLH) Kota Batam facilitates its employees with computers to support their work activities in the office. The activity of using this computer is carried out in a sitting manner by office employees. Employees work posture such as sitting posture and duration of using computer which doesn’t pay attention to the ergonomic side can causing muscle pain called Work-Related Musculoskeletal Disorders (WMSDs). The purpose of this study was to identify muscle complaints, analyze the risks of work posture and provide improvements to workers. The Rapid Office Strain Assessment (ROSA) method is used to determine the risk value of work activities using computers and sitting posture. In addition, the Nordic Body Map questionnaire is also used to determine the location of muscle complaints in workers. The results showed that 4 office employees have a risky work posture and there are 32 complaints of musculoskeletal pain felt by employees, where the most complaints were on the lower neck, waist and buttocks. Based on these results, it is necessary to improve employees work posture and work facilities.